A cross-country comparison of family carers experiences with residential aged care facilities during the COVID-19 pandemic. (October 2021) - Lion, Katarzyna M; Giebel, Clarissa; Chirico, Ilaria; Cations, Monica; Chattat, Rabih; Gabbay, Mark; Moyle, Wendy; Ottoboni, Giovanni; Valente, Marco
Abstract : Background: The number of research projects into residential aged care (RAC) during the COVID-19 pandemic is increasing, however there are limited data on the cross-country comparison of experiences residents living with dementia and their families. Our study aimed to 1) give an overview of the RAC restrictions and changes (visiting policy, governmental & health authorities' advice, service delivery) implemented during the pandemic in Australia, Italy and the UK and 2) and their impact on people with dementia in RAC facilities and their families. Methods: A total of 56 informal family carers of people with dementia residing in RAC took part in semi- structured interviews over the telephone or via Skype in Australia (n=6), Italy (n=25) and the UK (n=26) between July 2020 and March 2021. The interviews were recorded and translated verbatim. Transcripts were analysed by researchers in each country using thematic analysis, then combined across sites. Results: Inductive thematic analysis identified four overarching themes: 1) Adaptations implemented in RAC facilities due to the COVID-19 pandemic in Australia, Italy and the UK; 2) means of communication between RAC facility personnel, people with dementia living in RAC and family members; 3) impact of the implemented restrictions and changes in care provision due to the COVID-19 pandemic on people with dementia in RAC facilities and 4) impact of the implemented restrictions and changes in care provision due to the COVID-19 pandemic on families of people with dementia in RAC facilities. While differences between countries and facilities were identified, the restrictions and changes within the residential care system impacted families' well-being, increased their worries about care quality and safety of people with dementia. The consequences of a lack or modified services for people with dementia included noticeable physical and mental health changes. Although the majority of the facilities implemented some form of video-communication between families and residents, those solutions were unable to replace face-to-face contact. Conclusions: These findings demonstrate the need for implementing safe solutions which might facilitate more frequent in-person contact between families and residents with dementia preventing consequences in mental and physical health in both groups.